Medicinal Importance, Physicochemical Evaluation and Formulation Development of Polyherbal Anti-diabetic Tablet - Mandoria, Narendra; Dashora, Dr. Kamlesh (Journal of Medical Care Research and Review, 2021)
Herbal drugs have enormous therapeutic potential which can be explored through various beneficial drug delivery systems. In recent times the less use of herbal formulations due to lack of their standardization. These formulations reported to have various advantages over the solubility and reduced toxicity on the basis of physicochemical evaluation. The main objective of this present study was design, development and physicochemical evaluation of anti-diabetic polyherbal formulation. The overall objective of this work is to provide a complete knowledge and understanding of characteristics of a drug molecule before development of polyherbal tablets. Potentially active anti-diabetic herbs were used for developing tablets, these study should focus on physiochemical properties of new compound that affect drug performance and development of efficacious doses formulations or tablets. Phytochemical parameters for standardization of plants were according to standard methods and hydroalcoholic extract of Alstonia scholaris, Pterocarpus marsupium and Embelia ribes were used in the formulations. Key words: Polyherbal formulations, Preformulation studies, Physicochemical evaluation.